INTI: JARINGAN PERJUANGAN ORANG CINA-INDONESIA DI ERA PASCA REFORMASI - Untarawati, Dewik (Historia, 2024)
Chinese-Indonesians have long been the subject of discrimination and racism since the colonial period which lasted until the regime of Indonesia’s second president, Soeharto, later known as the New Order Era. Soeharto enacted the policy of assimilation which they were not allowed to have Chinese identity and should abandon their cultural heritage. The May ’98 Tragedy was the turning point to realize that their rights have been violated. After the Reformation, some groups of Chinese-Indonesians tried to voice their rights to seek justice as part of Indonesian citizens by forming the Chinese-Indonesian Association, or INTI. The organization aims to resolve Chinese-related issues, especially the issue of discrimination that has long been experienced by Chinese Indonesians. This paper will explore further the issues faced by Chinese Indonesians, what efforts they have made to solve the problems and the results of their struggle to get their rights back. The study uses a series of interviews with the founders of the Chinese Indonesian Association and literature studies related to this topic. The results of this study indicated that Chinese Indonesians faced some issues related to discrimination and racism in many facets of life including, politics, economy, society, and culture. Through the formation of INTI as a channel to voice their aspirations as well as to negotiate with a wide range of influenced figures, the government eventually enacted policies to restore their rights as Indonesian citizens. Keywords: Chinese-Indonesia Association; INTI; Tionghoa; Discrimination; Reformation